Trans-generation inheritance of methylation patterns in a tobacco transgene following a post-transcriptional silencing event - Lunerová-Bedrichová, Jana; Bleys, Annick; Fojtová, Miloslava; Khaitová, Lucie; Depicker, Anna; Kovarík, Ales (The Plant journal, 2008)
We have studied the inheritance of the epigenetic state of tobacco transgenes whose expression was post-transcriptionally silenced by an invertedly repeated silencer locus. We show that, in hybrids, the coding region of the target neomycin phosphotransferase (nptII) gene was almost exclusively methylated at CG configurations, and dense non-CG methylation occurred in the 3' untranslated region. Homologous sequences in the silencer locus were heavily methylated at both CG and non-CG motifs. After segregation of the silencer locus, the CG methylation but not the non-CG methylation of the target genes was transmitted to the progeny. In the segregants, we observed an overall increase of CG methylation in the target genes, associated with a re-distribution from the 3' end of the coding region towards the middle. This pattern was inherited with some fluctuation for at least two additional generations in the absence of a detectable T-DNA-derived small RNA fraction. Thus CG methylation is not cleared during meiosis and may be inherited over generations without RNA signals being present. These epi-allelic variants re-expressed the reporter gene immediately after segregation of the trigger, showing that relatively dense CG methylation (approximately 60-80%) imprinted on most of the coding region (>500 bp) did not reduce expression compared with the parental non-methylated locus. We propose that the genic CG methylation seen in euchromatic regions of the genome may originate from ancient post-transcriptional gene silencing events as a result of adventitiously produced methylation-directing RNA molecules.
Keywords: alely; Gene Expression Regulation, Plant; Alleles; DNA, Bacterial; typy dědičnosti; Plants, Genetically Modified; křížení genetické; RNA interference; Crosses, Genetic; Transgenes; transgeny; Inheritance Patterns; RNA Interference; DNA, Plant; DNA bakterií; tabák; metylace DNA; geneticky modifikované rostliny; DNA rostlinná; regulace genové exprese u rostlin; DNA Methylation; Nicotiana